Методика ситуационных заданий как инновационная технология формирования профессиональной этики будущих инженеров - Лапузина, Елена Николаевна (НТУ "ХПИ", 2005)
Some problems connected with Business Ethics and Career’s Growth are given in this article. of Business Ethics courses are studied in many universities of different countries. It is very important for our country because modern economics could not effectively function without serious ethic base.
Keywords: экономика рыночная; технологии информационные; технологии инновационные; кейс-метод; обучение ситуационное